2019
DOI: 10.1149/2.0611912jes
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Improvement Mechanism of Copper Oxide/BiVO4 Heterojunction Photoanodes for Solar Water Oxidation

Abstract: N-type BiVO 4 films coupled with p-type copper oxide nanoparticles were investigated as photoanodes for water oxidation. Compared with the BiVO 4 film, the Cu 2 O/BiVO 4 , CuO/BiVO 4 and Cu x O/BiVO 4 films all showed significantly improved photoelectrochemical water oxidation activity and stability. As expected, the radiative recombination of charge on the three kinds of copper oxide/BiVO 4 films was decreased due to the p-n junction effect between copper oxide and BiVO 4 . However, our investigations indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
4
17
0
Order By: Relevance
“…10b , the ITO/WO 3 /Cu 2 O/CuO photoanode has the smallest semicircle diameter compared with ITO/WO 3 /Cu 2 O and ITO/WO 3 photoanode, which directs that the transfer of charge carrier from the photoanode to the electrolyte is increased due to the CuO layer formation and better electrocatalytic activity for water oxidation of Cu x O compared with other photoanode. 30 EIS results have a great agreement with the absorbance of prepared photoanodes and their PEC performance. Overall, these results illustrate that enhanced electrocatalytic activity can facilitate better transport of charge carriers that is an important contributor to the superior PEC performance.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…10b , the ITO/WO 3 /Cu 2 O/CuO photoanode has the smallest semicircle diameter compared with ITO/WO 3 /Cu 2 O and ITO/WO 3 photoanode, which directs that the transfer of charge carrier from the photoanode to the electrolyte is increased due to the CuO layer formation and better electrocatalytic activity for water oxidation of Cu x O compared with other photoanode. 30 EIS results have a great agreement with the absorbance of prepared photoanodes and their PEC performance. Overall, these results illustrate that enhanced electrocatalytic activity can facilitate better transport of charge carriers that is an important contributor to the superior PEC performance.…”
Section: Resultssupporting
confidence: 70%
“… 9,21 The substantial enhancement in charge separation on ITO/WO 3 /Cu x O photoanode indicates that Cu x O coupling has a more obvious impact on the water oxidation kinetics of WO 3 than that on the surface-charge carriers' separation of ITO/WO 3 photoanode. 30 …”
Section: Resultsmentioning
confidence: 99%
“…As a cocatalyst for water oxidation recently reported, [42] the generated CuO can offset the detrimental effect of the conversion from Cu 2 S to CuO on the photoelectrochemical process. [43][44][45] These results suggest that the formation of SO chemical bonds between Cu 2 S and Fe 2 O 3 is crucial for the improvement and stability of the PEC performance. Based on linear sweep voltammetry (LSV) results, the applied bias photon to current efficiency (ABPE) value of each photoanode below thermodynamic potential of water oxidation (i.e., 1.23 V vs RHE) was calculated (Figure 3d).…”
Section: Pec Performance Of Cu 2 S/fe 2 O 3 Heterostructure Photoanodementioning
confidence: 99%
“…The Tafel slope of the Cu 3 Mo 2 O 9 /BiVO 4 film electrode during water oxidation is 95.2 and is 87.6 mV/dec for the Cu 3 Mo 2 O 9 film electrode, while the bare BiVO 4 film electrode has the highest Tafel slope of 128.1 mV/dec (Figure b). These observations revealed that Cu 3 Mo 2 O 9 coupling boosts the water oxidation kinetics of the BiVO 4 film electrode . For PEC water oxidation, the Cu 3 Mo 2 O 9 /BiVO 4 film photoanode also shows faster kinetics than the bare BiVO 4 film photoanode.…”
Section: Resultsmentioning
confidence: 82%